Interconnection and Significance: Exploration of Philosophy in the Life of the Poda Na Lima Batak Community in an Islamic Perspective - Iskandarsyah Siregar; Lyudmila Demidyuk (Lakhomi Journal Scientific Journal of Culture, 2023)
The essence of a nation's identity, rooted in its traditional values and philosophy, existed before the country was formed as a sovereign entity. This intrinsic connection with tradition forms the basic principles that form the foundation of nation building. Indonesia, like other countries, faces a number of challenges, often facing complexity and distortion in finding solutions to each unique situation. However, it is believed that by utilizing the philosophical foundations and traditional values inherent in its culture, Indonesia can navigate and resolve these problems effectively. The essence of this approach is the recognition of the important role of philosophy in guiding societal norms and behavior. In particular, the adoption of religious values, such as those contained in Islam, has great potential to ground society in the eternal truths represented in traditional customs. Islam, characterized by its universal nature as a religion of “rahmatan lil’alamin” (mercy for all nature), offers a comprehensive framework that can address various aspects of human existence. This study emphasizes the importance of revitalizing the life orientation of the community, especially the Batak tribe, by aligning it with the principles contained in the Poda Na Lima philosophy. By explaining the relationship between their identities as Muslim and Batak, individuals can bring greater resonance and authenticity to the structures and infrastructure of their society. Using a qualitative approach rooted in critical discourse analysis, this research aims to reveal the complex relationship between traditional philosophy, religious teachings, and contemporary challenges. Through examination of the Poda Na Lima framework, which consists of five basic principles, it becomes clear that these principles contain deep wisdom and serve as a guide to community behavior.